THE IMPACT OF INTERNATIONAL JUDICIAL INSTITUTIONS ON THE DEVELOPMENT OF LEGAL SYSTEMS IN WEST AFRICA (CASE STUDY OF BURKINA FASO) - Dima Sеrgе, Patrick (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: this article examines the impact of international judicial institutions on the development of the legal systems of West Africa, namely Burkina Faso. Research methods: synthesis, analysis, formal-legal, comparative-legal. Results: the impact of international judicial institutions on the development of West African legal systems, particularly in Burkina Faso, was assessed from the perspective of international conflict resolution and its impact on the rule and development of democracy in Africa, and the main grounds for conflict resolution were identified: Discussion: this article reveals the influence of international judicial institutions on the development of the legal systems of West African countries, often due to the political and social realities of the countries. These countries have generally succeeded in developing a colonial system of justice. The legal systems of West African countries derive from different traditions inherited from colonization. They have also been influenced by numerous customs and religious norms which influence the structure of the judicial system in each country. The region is now collectively developing under the aegis of the Economic Community of West African States (ECOWAS).